Alterations in DNA methylation and airway hyperreactivity in response to in utero exposure to environmental tobacco smoke. (10th November 2015) - Lee, Joong Won; Jaffar, Zeina; Pinkerton, Kent E.; Porter, Virginia; Postma, Britten; Ferrini, Maria; Holian, Andrij; Roberts, Kevan; Cho, Yoon Hee
Abstract: Growing evidence indicates that prenatal exposure to maternal smoking is a risk factor for the development of asthma in children. However, the effects of prenatal environmental tobacco smoke (ETS) exposure on the genome and lung immune cells are unclear. This study aims to determine whether in utero ETS exposure alters DNA methylation patterns and increases airway hyperreactivity (AHR) and inflammation. Pregnant C57BL/6 mice were exposed daily to a concentration of 1.0 mg/m 3 ETS. AHR was determined in the 6-week-old offspring by measurement of airway resistance. Global and gene promoter methylation levels in lung DNA from offspring were analyzed by luminometric methylation and pyrosequencing assays, respectively. Offspring exposed to ETS showed a marked increase in the number of alveolar macrophages in the bronchoalveolar lavage fluid and level of IL-13 in the airways compared with offspring of filtered-air exposed dams (controls). ETS exposure significantly augmented AHR compared with controls. In the methylation analysis, ETS-exposed offspring had a significantly lower level of global DNA methylation than the controls. We observed a significant increase in IFN-γ, and significant decrease in IL-13 methylation levels in the ETS group compared with controls. Collectively, these data suggest that in utero ETS exposure increases the risk of pulmonary inflammation and AHR through altered DNA methylation, but additional studies are needed to fully determine the causal link between changes in methylation and cytokines levels, as well as AHR.